(untitled) (Annals of Bangladesh Agriculture, 2022)
Transplanted aman rice suffers from frequent flash flood damage in northern Bangladesh and thus grain yield decreases. An experiment was conducted at the RDRS Farm, Rangpur, Bangladesh to evaluate production opportunity and income generation from growing ratoon rice in between boro and aman seasons during May to July in fallow land as additional harvests. Ratoon seedlings of ACI-2 boro hybrid rice was transplanted and tested against the performance of conventional transplanted BR11 and BRRI dhan46. BR11 gave higher grain yield and profit than ratoon cropping. However, ratoon crop required only 75-80 days for maturity. Thus, it would be possible to incorporate rice ratoon cropping in fallow lands immediately after harvest of boro rice in April- May as additional crop. After harvests of the ratoon rice, farmers can grow traditional aman varieties as conventional practice. If ratoon of ACI-2 (hereafter ratoon rice)-BRRI dhan46 cropping system is practiced then total grain yield from the system was 8.42 t ha-1, which was almost double than conventional BR11 or BRRI dhan46 cultivation. Total net income of boro and ratoon rice-BRRI dhan46 system was also higher (Tk 55,090 ha-1) compared to traditional BR11 aman rice cultivation (Tk 35,802 ha-1). The overall result indicated that just immediate after boro rice harvests, growing rice from ratoon seedlings of ACI-2 followed by BRRI dhan46 in aman season provided higher net profit than traditional cultivation of BR11. The result also implies that growing rice by using ratoon seedlings can ensure three harvests (boro rice-ratoon rice-aman rice) in the same year instead of growing two traditional rice (boro rice-aman rice) crops in a year with additional net profit of Tk 19,288 ha-1 year-1. Moreover, use of rice ratoon seedlings might help farmers in intensification of crop in flash flood prone areas of the country. Ann. Bangladesh Agric. (2021) 25 (1) : 33-41